Opportunities and constraints for dried dessert banana (Musa spp.) export in Uganda - Asten, Piet J.A. van; Florent, D.; Apio, M.S. (2010)
In Uganda, ‘Sukali Ndizi’ (syn. ‘Apple banana’, AAB genome) are dessert bananas that are being processed into dried slices for export. Surveys with five Ugandan exporting companies suggested that export prices of dried banana slices were favorable ($6.5–12/kg), but strongly depended on the quality and certification of the product. Major bottlenecks to further expand the export seem not to be related to a lack of demand in Europe, but to the fact that quantities and quality of the exported produce are insufficient. Exporters indicated that one of the major constraints related to producing sufficient volumes is the spread of Fusarium wilt (Fusarium oxysporum f. sp. cubense), which increasingly affects ‘Sukali Ndizi’ production. They also indicated that other dessert bananas on the Ugandan market (e.g., ‘Gros Michel’ and ‘Cavendish’, both AAA genome) are not processed into dried slices because the processed product is largely inferior to that of ‘Sukali Ndizi’ in terms of taste. This study compares drying, color and taste characteristics (texture, acidity, sugar content and color) of seven alternative Fusarium wilt-resistant banana cultivars (‘FHIA-01’, AAAB genome; ‘FHIA-17’, AAAA genome; ‘FHIA-23’, AAAA genome; ‘FHIA-25’, AAB genome; ‘SH-3640/10’, AAAB; ‘Yangambi Km 5’, AAA; ‘Kikundi’, AAA-EA genome) with ‘Sukali Ndizi’. European consumers rated the taste characteristics of ‘FHIA-01’ at least as good as ‘Sukali Ndizi’ and appreciated its color more than the latter. The taste and color of other cultivars were generally rated inferior (‘SH-3640/10’ > ‘Kikundi’ > ‘Yangambi Km5’ > ‘FHIA-17’ > ‘FHIA-23’ > ‘FHIA-25’). ‘FHIA-01’ and ‘Sukali Ndizi’ also had the highest fresh pulp dry matter content (32 and 36%, respectively) compared to other cultivars (27%) and were less sticky than other cultivars, which facilitated the processing and packing of the banana slices. This study shows there is potential to further exploit the dried dessert banana export market using Fusarium wilt-resistant cultivars.